2021
DOI: 10.1007/s10182-021-00413-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the change in soccer’s home advantage during the Covid-19 pandemic using bivariate Poisson regression

Abstract: In wake of the Covid-19 pandemic, 2019–2020 soccer seasons across the world were postponed and eventually made up during the summer months of 2020. Researchers from a variety of disciplines jumped at the opportunity to compare the rescheduled games, played in front of empty stadia, to previous games, played in front of fans. To date, most of this post-Covid soccer research has used linear regression models, or versions thereof, to estimate potential changes to the home advantage. However, we argue that leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Thus, spectators can significantly contribute to determine the dynamics and the outcomes of professional football matches." (p. 1) Benz ( 2021 )* No change in home advantage : Mixed findings indicate that changes of home advantage in ghost games is league dependent, indicating a complex causal mechanism "In some leagues, evidence is overwhelming that HA declined for both yellow cards and goals. Alternatively, other leagues suggest the opposite, with some evidence that HA increased."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, spectators can significantly contribute to determine the dynamics and the outcomes of professional football matches." (p. 1) Benz ( 2021 )* No change in home advantage : Mixed findings indicate that changes of home advantage in ghost games is league dependent, indicating a complex causal mechanism "In some leagues, evidence is overwhelming that HA declined for both yellow cards and goals. Alternatively, other leagues suggest the opposite, with some evidence that HA increased."…”
Section: Resultsmentioning
confidence: 99%
“…For the international scientific community, however, it may be more important to bundle, to synthesize and to clarify the findings from this field in the (presumable) dusk of the pandemic in the fall of 2021. In particular, there are some inconsistencies across studies regarding the reported effects of the ghost games on the home advantage, which can be tracked down to different methodological approaches, inconsistencies across leagues and small or particular samples (see e.g., Benz and Lopez 2021 ). To this end, we provide a comprehensive overview of all empirically relevant studies conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, no differences in external or internal workloads were found to exist between home and away games. It is important to consider that COVID restrictions prevented or reduced fan attendance for all games utilized herein, which may have contributed to the absence of a "home advantage" [41,42]. Though, other contextual factors, including game result, opponent ranking, and final score differential each seemed to modify workload trends in varying ways.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted during a shortened training and competitive season, among many other abnormalities as compared to a normal season. As mentioned previously, a majority of games were completed in the absence of fans, which may have diminished the "home advantage" that has been found elsewhere [41,42,54,55]. Aside from the increased consistency and time between scheduled matches, numerous modifications during the COVID-19 sports season imposed additional challenges on team success [56].…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The performance of the models has been evaluated on two disjoint test sets, the seasons of 2020/21 and 2021/22. They are treated separately because most games in the 2020/21 edition were played behind closed doors owing to the COVID-19 pandemic, which might significantly affect home advantage (Benz and Lopez, 2021;Bryson et al, 2021;Fischer and Haucap, 2021).…”
Section: The Simulation Of Match Outcomesmentioning
confidence: 99%